Contrasting age related changes in autism spectrum disorder phenomenology in Cornelia de Lange, Fragile X, and Cri du Chat syndromes: Results from a 2.5 year follow‐up. (18th May 2015) - Cochran, Lisa; Moss, Joanna; Nelson, Lisa; Oliver, Chris
<x xml:space="preserve">Abstract</x> Little is known about the way in which the characteristics of autism spectrum disorder (ASD) develop and manifest across the age span in individuals with genetic syndromes. In this study we present findings from a two and a half year follow‐up of the characteristics associated with ASD in three syndromes: Cornelia de Lange (CdLS), Fragile X (FXS), and Cri du Chat (CdCS). Parents and carers of 251 individuals (CdLS = 67, CdCS = 42, and FXS = 142) completed the Social Communication Questionnaire (SCQ) at Time 1 (T1) and again two and a half years later (T2). The FXS and CdLS groups were more likely to meet the cut‐offs for both autism and ASD and show greater severity of ASD related behaviors, at both T1 and T2, compared to the CdCS group. Older individuals (>15yrs) with CdLS were more likely to meet the cut off for ASD than younger individuals (≤ 15yrs) with the syndrome and more likely to show greater severity of social impairments. In FXS repetitive behaviors were found to become less prominent with age and in CdCS social impairments were reported to be more severe with age. There were no significant changes between T1 and T2 in the severity of ASD characteristics in the CdCS and CdLS groups. The FXS group showed significantly fewer repetitive behaviors and less severe impairments in social interaction over this time frame. The findings suggest that while there may be similarities in overall severity and presentation of ASD characteristics in CdLS and FXS, these characteristics have divergent patterns of development within these groups. © 2015 Wiley Periodicals, Inc.